Heteroleptic tris-chelate ruthenium(II) complexes of N, N-disubstituted-N′-acylthioureas: Synthesis, structural studies, cytotoxic activity and confocal microscopy studies. (18th April 2017) - Barolli, João P.; Maia, Pedro I.S.; Colina-Vegas, Legna; Moreira, Jane; Plutin, Ana M.; Mocelo, Raúl; Deflon, Victor M.; Cominetti, Marcia R.; Camargo-Mathias, Maria I.; Batista, Alzir A.
Graphical abstract: New heteroleptic tris-chelate ruthenium(II) complexes containing thiourea ligands were obtained and characterized on the basis of various methods including the single crystal X-ray technique. The stability of the complexes was investigated electrochemically by cyclic voltammetry. The cytotoxicity of the compounds was evaluated against tumor cells and normal fibroblast cells. A remarkable cell growth inhibition was observed for most of the compounds with lower IC50 values than cisplatin. Confocal microscopy images of the control tumor cells were compared with those of tumor cells treated with one of the complexes, supporting that these compounds are able to cause cell death by affecting the actin filaments instead of binding to DNA. Abstract: Ruthenium complexes have been assessed as anti-tumor agents against cancer cells. In this project, new heteroleptic ruthenium(II) complexes with general formulae [Ru(L)(bipy)(dppb)](PF6 ) (where L =  N, N -disubstituted- N ′-acylthiourea, bipy = 2, 2′-bipyridine and dppb = 1, 4-bis(diphenylphosphino)butane) were synthesized and characterized by elemental analysis, IR and NMR ( 1 H and 31 P{ 1 H}) spectroscopies, molar conductivity measurements and single crystal X-ray diffractometry. The IR and NMR data suggest the coordination of the ligands to the Ru(II) metal center through the thiocarbonyl and carbonyl groups. The structures of the new complexes were further studied by X-ray crystallography, which confirmed the coordination of the ligands with the metal through the sulfur and oxygen atoms, leading to the formation of distorted octahedral complexes. The N, N -disubstituted- N ′-acylthioureas and their complexes were screened with respect to their in vitro cytotoxicity. All compounds exhibited considerable antiproliferative activity against MCF-7 (human breast tumor cells ATCC HTB-26), DU-145 (human prostate tumor cells ATCC HTB-26), and relatively low toxicity against fibroblast L929 cells (health cell line from mouse ATCC CCL-1). A preliminary study regarding the mechanism of action of these compounds by confocal microscopy shows alterations of the actin filaments leading to modifications in cytoskeletal supporting the cell death and that the cell nucleus is not main target of these complexes.